2018
DOI: 10.1186/s12884-018-1782-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-pregnancy hair dye exposure on infant birth weight: a nested case-control study

Abstract: BackgroundLimited evidences were reported about the risk of pre-pregnancy hair dye use or irregular menstruation with abnormal birth weight during pregnancy, and their joint effects were also unknown. The aim of our study was to explore whether the pre-pregnancy exposure of hair dye and irregular menstruation were associated with the risk of abnormal birth weight.MethodsWe conducted a nested case-control study from a prospective cohort of 6203 pregnant women. Low birth weight study included 315 mother-infant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…16 In a separate study, ever use of dark hair dyes during pregnancy was associated with higher odds of delivering a low-birth weight infant among 315 Chinese mother-infant pairs. 17 Observed associations between hair products and health outcomes may also be due to behavior change related to hair product use. For instance, products only result in temporary hair maintenance and styling; the altered hair can readily revert to an undesired style or state due to environmental humidity or natural biological processes like sweating from physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…16 In a separate study, ever use of dark hair dyes during pregnancy was associated with higher odds of delivering a low-birth weight infant among 315 Chinese mother-infant pairs. 17 Observed associations between hair products and health outcomes may also be due to behavior change related to hair product use. For instance, products only result in temporary hair maintenance and styling; the altered hair can readily revert to an undesired style or state due to environmental humidity or natural biological processes like sweating from physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that LBW is more frequent in women who dyed their hair in the preconception period or third trimester. Jiang et al also showed an association between pre-pregnancy hair dye use and increased risk of LBW [4]. Other studies investigated LBW in the hairdressers who have occupational exposure to the hair dye chemicals.…”
Section: Discussionmentioning
confidence: 99%
“…It is not clear whether hair color would affect the fetus or not. Studies showed a possible association between hair coloring during pregnancy, and low birth weight, neuroblastoma, and leukemia in the offspring [4][5][6][7]. There is a report for increased neonatal abnormalities in mothers who used chlorinated solvents and glycol ether for hair dyeing during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, hair oils are typically used more frequently and are not rinsed out as quickly compared to dyes and relaxers [ 15 ]. In a nested case–control study of Chinese mother-infant pairs ( n = 210 controls, n = 105 cases), use of hair dyes prior to conception was associated with greater odds of delivering a low-birth weight infant (odds ratio (OR): 1.71; 95% CI: 1.01, 2.92) [ 32 ]. However, data on dye use during pregnancy were not collected.…”
Section: Discussionmentioning
confidence: 99%